(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of the study is to reveal the effect of the constructivist learning Model on the achievement and reflective thinking of the fifth grade literary Preparatory students in History subject. A random sample was chosen which consisted of 64 students divided into experimental and control groups, each group consisted of 32 students. The experimental group was taught via the constructivist learning model, and the control group was taught via the traditional method. The experiment was lasted for Eight weeks, each week taught two lessons. The researcher adopted the experimental design with partial control. The two groups were equalized statistically. The researcher used two instruments, the achievement test and the reflective thinking test. The results showed that the students of the experimental group that studied via the constructive learning model were superior to the students in the control group which studied via the traditional method in the achievement test and the reflective thinking test. This refers that teaching via constructivist learning Model is considered a good method and has a positive impact on teaching. When measuring the effect size of the independent variable (constructivism learning model) in the two dependent variables (achievement and reflective thinking), the results showed that the effect size was (big).